Effect of Bay Leaf Extract (Syzygium polyanthum) on Blood Glucose, Malondialdehyde, and Insulin Levels in Animal Models of Diabetes: A Systematic Review - Brian Nathaniel Santoso; Maftuchah Rochmanti; Lina Lukitasari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion or action. Long-term antidiabetic therapy may cause adverse effects, highlighting the need for safer alternative treatments. Syzygium polyanthum (bay leaf) contains various bioactive compounds with antidiabetic and antioxidant activities. This study aimed to evaluate the effects of Syzygium polyanthum leaf extract on blood glucose, malondialdehyde (MDA) and insulin levels in diabetic rat models through a systematic review. This review was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. Literature searches were performed in PubMed, Scopus, ScienceDirect, and Google Scholar. Included studies were experimental in vivo studies using diabetic rat models that assessed the effects of Syzygium polyanthum extract on blood glucose, insulin, and/or MDA levels. Risk of bias was evaluated using the CAMARADES tool. The results showed that administration of Syzygium polyanthum extract at doses of 250–500 mg/kg body weight consistently reduced blood glucose levels, accompanied by increased insulin levels and decreased MDA levels. These findings indicate that Syzygium polyanthum leaf extract has potential antidiabetic and antioxidant effects in animal models of diabetes